Over-The-Scope Clip for the Immediate Management of Stapfer Type-1 Duodenal Perforation during Endoscopic Retrograde Cholangiopancreatography - Kathryn Gazelakis; Grace Lovett; Robert Chen; Yahya Al-Habbal; Kumanan Nalankilli (Case Reports in Gastroenterology, 2022)
Iatrogenic Stapfer type-1 duodenal perforations during endoscopic retrograde cholangiopancreatography (ERCP) typically necessitate surgical management and carry significant morbidity and mortality risk. Here, we present a case of a large duodenal perforation during ERCP managed endoscopically with an over-the-scope clip (OTSC) and describe the subsequent post-procedural management. An 80-year-old woman presented to the emergency department with acute cholangitis. Abdominal ultrasound scan revealed a dilated biliary tree with echogenic material in the common hepatic and intrahepatic ducts. The patient proceeded to ERCP, where filling defects consistent with stones were found in the proximal main bile duct on cholangiogram. Stone retrieval was complicated by a large iatrogenic perforation of the infero-lateral duodenal wall, distal to the major ampulla (Stapfer type-1). Following unsuccessful attempts to close the defect using through-the-scope clips, a decision was made to attempt closure endoscopically using an OTSC. The duodenoscope was exchanged for a forward-viewing gastroscope mounted with the OTSC. The perforation defect was fully suctioned into the cap and the clip was successfully deployed. Subsequent on-table fluoroscopy with contrast injection did not demonstrate any extra-luminal contrast leak. The patient developed a post-procedure infra-duodenal collection, however, made a complete recovery with bowel rest, negative pressure regulation at the site of the OTSC using a dual-lumen nasogastric/nasojejunal feeding tube and intravenous piperacillin-tazobactam. Thus, OTSCs potentially offer a safe and effective endoscopic treatment modality for the immediate management of ERCP-related Stapfer type-1 duodenal perforations.